Answer:
- 386.6 kJ/mol.
Step-by-step explanation:
- To solve this problem, we can use Hess's Law:
ΔHrxn = ΣΔHf(products) - ΣΔHf(reactants)
- For this reaction: Ca(s)+ 2H₂O(l) → Ca(OH)₂(s) + H₂(g),
∴ ΔHrxn = ΣΔHf(products) - ΣΔHf(reactants) = [ΔHf(Ca(OH)₂(s)) + ΔHf(H₂)(g)] - [ΔHf(Ca)(s) + 2*ΔHf(H₂O)(l)].
ΔHf(Ca(OH)₂(s)) = - 985.2 kJ/mol, ΔHf(H₂)(g) = 0.0 kJ/mol, ΔHf(Ca)(s) = 0.0 kJ/mol, ΔHf(H₂O)(l) = - 285.8 kJ/mol.
∴ ΔHrxn = ΣΔHf(products) - ΣΔHf(reactants) = [ΔHf(Ca(OH)₂(s)) + ΔHf(H₂)(g)] - [ΔHf(Ca)(s) + 2*ΔHf(H₂O)(l)] = [(- 985.2 kJ/mol) + (0.0 kJ/mol)] - [(0.0 kJ/mol) + 2*(- 285.8 kJ/mol)] = - 386.6 kJ/mol.